Mengkaji Tahap Kesedaran Pengguna Terhadap Risiko Pembelian di Atas Talian dalam kalangan Pelajar FPTP - Yah, Tabita yah; Mohd Angsor, Mohd Asmadi (Research in Management of Technology and Business, 2023)
In compliance with the Movement Control Order (MCO) that was launched in March 2020, consumers have changed their purchasing methods which now fully use online platforms, one of which is online business to stop the spread of this Covid-19 epidemic. Online shopping is chosen as a quick way to buy necessities without having to queue at the counter and customers can browse the items they want to buy and compare brands, prices and quality before placing an order. However, consumers who make a transaction for the purchase of a desired item are more susceptible to various risks. Therefore, this study was conducted to examine the objectives related to the level of consumer awareness of purchase risks and the level of awareness of legal issues in online purchases along with the relationship to the risks that consumers face. This study focused on FPTP students at UTHM as respondents for this study. A total of 335 respondents’ data was collected through a questionnaire that was distributed online. Correlation analysis was done using SPSS software and the results showed r=0.680 while the range of p=.000 where p>0.01 is positive, then H1: there is a significant relationship between legal issues and consumer awareness of the risks of buying online, supported. The mean value for the independent variable is = 4.05 while for the dependent variable is = 4.02. The results of this study have shown that consumers’ awareness of the risks of online purchases is strongly emphasized for security in terms of merchant fraud and privacy of personal information. This study also gives awareness to users to be aware of the risks that occur online and the enforcement authorities need to increase alternatives to protect the rights of users.